Relationship Following Training and Achievement Motivation with Work Satisfaction Learning Citizens in Mandir Institution Courses and Training of Tanjung Balai City - Tien Rafida; Toni Julham (Budapest International Research and Critics University, 2020)
The research aims to find out: (1) a significant positive relationship between participating in training with job satisfaction of learning citizens, (2) a significant positive relationship between achievement motivation and job satisfaction and (3) a significant positive relationship between participating in training and achievement motivation together with job satisfaction of citizens learning. The study population was all citizens studying the Tanjung Balai City Course and Training Institute with a total of 72 people. The entire population was sampled as a study. The research instrument used was a Likert scale questionnaire. Requirement test is performed to test the normality, linearity, and independence of the independent variables. Data analysis techniques used correlation and regression and simple correlation and regression and multiple correlations at the significance level α = 0.05. The research findings show: (1) there is a positive and significant relationship between training and job satisfaction It means that the higher and more positive the training, the higher and more positive job satisfaction by making an effective contribution of 20.00%. (2) There is a positive and significant correlation between achievement motivation and job satisfaction. This means that the higher and more positive achievement motivation, the higher and more positive job satisfaction by making an effective contribution of 9.90%. And (3) there is a positive and significant effect together between participating in training and achievement motivation with job satisfaction. This means that the higher and more positive training and achievement motivation, the higher and more positive job satisfaction by making an effective contribution of 30.20%.